2009
DOI: 10.3382/ps.2009-00165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginger root (Zingiber officinale) processed to different particle sizes on growth performance, antioxidant status, and serum metabolites of broiler chickens

Abstract: A study using 144 one-day-old Arbor Acres broilers was conducted to assess the effects of dried ginger root (Zingiber officinale) that was processed to particle sizes of 300, 149, 74, 37, and 8.4 microm on growth performance, antioxidant status, and serum metabolites of broiler chickens. The birds were housed in 24 wire cages in an environmentally controlled room. Dietary treatments were no supplementation (control) and supplementation with ginger root processed to 5 particle sizes at the level of 5 g/kg of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
137
2
21

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(184 citation statements)
references
References 41 publications
24
137
2
21
Order By: Relevance
“…These results are consistent with those of Zhang et al [29] in broiler chickens treated with ginger rhizomes powder at doses of 5 g/kg of diet. Conversely, other researchers recorded a significant decrease in serum proteins and globulins in broilers treated with ginger roots powder [20] [30].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those of Zhang et al [29] in broiler chickens treated with ginger rhizomes powder at doses of 5 g/kg of diet. Conversely, other researchers recorded a significant decrease in serum proteins and globulins in broilers treated with ginger roots powder [20] [30].…”
Section: Discussionsupporting
confidence: 93%
“…Activity of GSH-Px was detected with 5, 5'-dithiobis-ρ-nitrobenzoic acid by measuring the OD of the reaction solution at 412 nm. One unit of GSH-Px activity was defined as the amount of enzyme per 0.1 mL of serum that would catalyze the conversion of 1 μmol L −1 of GSH to oxidized GSH at 37°C in 5 min (Zhang et al, 2009). The concentration of Malondialdehyde (MDA) was determined with a MDA Assay Kit A003 (Institute of Biological Engineering of Nanjing Jianchen, Nanjing, China).…”
Section: Assay Of Antioxidant Enzymes In Serummentioning
confidence: 99%
“…For example, Taylor (2001) showed that the use of ginger and ginger powders significantly increased body weight and improved feed conversion compared to birds fed with control diet. In contrast, Zhang et al (2009) examined the effect of processed ginger with different size on growth performance and showed that the ginger additive had no significant effect on the feed efficiency, while body weight and daily weight gain of birds fed with ginger supplements were higher than control group. It is also reported that serum cholesterol levels in broilers can be decrease 0.4 or 0.6% ginger powder.…”
Section: Introductionmentioning
confidence: 98%